Sustainability reporting and management control system: A structured literature review - ABM Fazle Rahi; Jeaneth Johansson; Arne Fagerström; Marita Blomkvist (Journal of Risk and Financial Management, 2022)
The purpose of this paper is to contribute to the management accounting literature by reviewing how previous studies conceptualised the relationship between sustainability reporting and management control systems, analysing the main themes and discussing potential future developments of the sustainability reporting and management control systems (SRMCS) research agenda. This study builds on the structured literature review method by categorising and synthesising 15 years of research into the topic 'sustainability reporting and management control'. Approximately 500 relevant articles were identified in the first round of searching Google Scholar and Scopus with the selected keywords, but after filtering and manual assessment, 45 articles were selected for the full review. Coding reliability was maintained with the K-alpha test. Our findings divulge that the researcher looks at the management control and the sustainability reporting agenda with just one eye. They either focus on management control or sustainability reporting. Very little research focuses on relationships. In addition, from the methodological point of view, we found that qualitative case studies and interviews dominate the field, together with commentary papers. We proposed a framework showing a complex and multifaceted relationship (a spider diagram) to conceptualise the synthesis of the literature. This framework is intended as a blueprint for the relationship between sustainability reporting and management control in order to design and redesign a company's internal strategies on management control systems (MCS).
Keywords: 650; integrated report; management accounting; management control system; structured literature review; sustainability report